2022
DOI: 10.1155/2022/4900917
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antibacterial and Antioxidant Activities of Stem Bark Essential Oil and Extracts of Solanecio gigas

Abstract: Herbal medication developed from natural resources has to have antibacterial and antioxidant effects. The aim of this research is to look at the chemical makeup of Solanecio gigas (S. gigas) stem bark essential oil (EO), as well as the effectiveness of EO and extracts (chloroform, ethyl acetate, and methanol) against human pathogenic bacteria and their antioxidant activity. The GC-MS analysis identified 23 components, accounting for 98.7% of the total oil containing Methylene chloride (49.2%), sabinene (10.5%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
4
7
0
Order By: Relevance
“…are implicated in the toxicity of microorganisms through disruption of cell membranes and spontaneous out ow of intracellular components that can potentially culminate in the death of pathogenic bacteria strains [21,42]. The pronounced antibacterial activity of the MRE is consistent with the TPC and TFC as reported elsewhere [40].…”
Section: Antibacterial Activity Of P Varians Root Extractssupporting
confidence: 71%
See 3 more Smart Citations
“…are implicated in the toxicity of microorganisms through disruption of cell membranes and spontaneous out ow of intracellular components that can potentially culminate in the death of pathogenic bacteria strains [21,42]. The pronounced antibacterial activity of the MRE is consistent with the TPC and TFC as reported elsewhere [40].…”
Section: Antibacterial Activity Of P Varians Root Extractssupporting
confidence: 71%
“…Overall, relatively highest antibacterial activities were recorded by the MRE against Klebsiella pneumoniae (20 ± 0.04 mm) and Staphylococcus aureus (17 ± 0.12 mm); and ARE on Escherichia coli (17 ± 0.15 mm). Consistent with this, Yitayeh et al, [40] also reported the superior antibacterial activity of the methanolic Solanecio gigas stembark extract as compared to the less polar ethyl acetate and chloroform extracts on the same bacteria strains. The signi cant and better antibacterial activity of the MRE of P. varians might be attributed to the presence of high concentrations of avonoids, alkaloids, phenols, terpenoids, tannins, etc.…”
Section: Antibacterial Activity Of P Varians Root Extractssupporting
confidence: 53%
See 2 more Smart Citations
“…The other Asteraceae plants in our studies with reported bioactivities are Lactuca inermis Forssk and Solanecio gigas (Vatke) C.Jeffrey ( Janbaz et al, 2013 ). Both of them are known to have antimicrobial activity against a variety of microbes ( Molla Yitayeh and Monie Wassihun, 2022 ).…”
Section: Resultsmentioning
confidence: 99%